Evaluación de tres herbicidas pre-emergentes aplicados al cultivo de maíz (Zea mays) sembrado en la finca experimental “La María” en época seca. - Meza Méndez, José Leonel (2019)
The weeds cause problems such as the subtraction of nutrients, water and sunlight, this competition being vitally important during the first five weeks. Pre-emergent herbicides are herbicides that are applied after planting, but before weeds and cultivation emerge, it is for that reason that they are so called. These products are characterized by eliminating weeds in their germination and newly emerged process, this avoids weed-cultivation competition during the latter's vegetative periods due to water, light and nutrients. the objective of evaluating three pre-emergent herbicides that were applied to the cultivation of corn (Zea mays) planted in the experimental farm "La María" in dry season. For which the trial was divided into four treatments: pre-emergent: STOMP AQUA, PROWL TOP, PELION and a control treatment, for which a randomized complete block design (BCA) was performed with four repetitions in each treatment and with a frame of 0.50 mx 0.50 m, four evaluation points were marked in each treatment, in which 20 days after the application, the first evaluations were carried out which consisted in the identification of certain weeds associated with the cultivation of corn and the number of individuals present of each species; the degree of phytotoxicity in the culture was evaluated. The results allow us to show that the Herbicide treatment. STOMP AQUA was the one that stood out from the rest of treatments with averages of 16, 17, 17, 14, 20, 23 of weeds present at 20, 25, 30, 35, 40 and 45 days after the applications respectively, the Herbicide. PELION was the treatment with the lowest phytotoxic effect in the crop with an index of 1.3, which in turn with regard to fixed costs, it was determined that with a value of $ 31.74 is lower compared to other treatments. It is recommended to test mixtures with pre-emergent herbicides of other chemical families of the same company to find a greater control efficiency of the different weed species associated with corn cultivation Keywords: Herbicide, pre-emergent, control, Zea mays, weed